E11/Podoplanin Protein Stabilization Through Inhibition of the Proteasome Promotes Osteocyte Differentiation in Murine in Vitro Models. Issue 6 (28th December 2015) - Staines, Katherine A.; Prideaux, Matt; Allen, Steve; Buttle, David J.; Pitsillides, Andrew A.; Farquharson, Colin
Abstract : The transmembrane glycoprotein E11 is considered critical in early osteoblast–osteocyte transitions (osteocytogenesis), however its function and regulatory mechanisms are still unknown. Using the late osteoblast MLO‐A5 cell line we reveal increased E11 protein/mRNA expression ( P < 0.001) concomitant with extensive osteocyte dendrite formation and matrix mineralization ( P < 0.001). Transfection with E11 significantly increased mRNA levels ( P < 0.001), but immunoblotting failed to detect any correlative increases in E11 protein levels, suggestive of post‐translational degradation. We found that exogenous treatment of MLO‐A5 and osteocytic IDG‐SW3 cells with 10 μM ALLN (calpain and proteasome inhibitor) stabilized E11 protein levels and induced a profound increase in osteocytic dendrite formation ( P < 0.001). Treatment with other calpain inhibitors failed to promote similar osteocytogenic changes, suggesting that these effects of ALLN rely upon its proteasome inhibitor actions. Accordingly we found that proteasome‐selective inhibitors (MG132/lactacystin/ Bortezomib/Withaferin‐A) produced similar dose‐dependent increases in E11 protein levels in MLO‐A5 and primary osteoblast cells. This proteasomal targeting was confirmed by immunoprecipitation of ubiquitinylated proteins, which included E11, and by increased levels of ubiquitinylated E11 protein upon addition of the proteasome inhibitors MG132/Bortezomib. Activation of RhoA, the small GTPase, was found to be increased concomitant with the peak in E11 levels and its downstream signaling was also observed to promote MLO‐A5 cell dendrite formation. Our data indicate that a mechanism reliant upon blockade of proteasome‐mediated E11 destabilization contributes to osteocytogenesis and that this may involve downstream targeting of RhoA. This work adds to our mechanistic understanding of the factors regulating bone homeostasis, which may lead to future therapeutic approaches. J. Cell. Physiol. 231: 1392–1404, 2016. © 2015 The Authors. Journal of Cellular Physiology published by Wiley Periodicals, Inc.